2019
DOI: 10.1016/j.colsurfb.2018.09.023
|View full text |Cite
|
Sign up to set email alerts
|

In situ phase transition of microemulsions for parenteral injection yielding lyotropic liquid crystalline carriers of the antitumor drug bufalin

Abstract: In this work, we use the small angle X-ray scattering (SAXS) method for controlled preparation of in situ forming sustained-release carriers of the antitumor drug bufalin (BUF), which has very poor solubility and a considerable cardiotoxicity in a non-encapsulated state. To that aim, we exploit the pseudo-ternary phase diagram of an oil(O)/surfactant(S)/water(W) system containing medium chain capric/caprylic triglycerides (MCT) and a co-surfactant blend of Macrogol (15)-hydroxystearate (Solutol HS 15) and sorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 44 publications
0
22
0
2
Order By: Relevance
“…In fact, hydrophilic drugs with different molecular weights, such as fluorescein, could be loaded into a liquid crystalline aqueous compartment and provided a cumulative drug release through the surfactant membrane, by a linear relationship between drugs and the square root of time, which has been also considered to be the Higuchi diffusion-controlled release kinetic [9]. Previous data demonstrated that the release of diclofenac salts from lyotropic liquid crystalline nanocarriers [73], as well as the release of charged molecules from lipid cubic phases, in a quasi-equilibrium process [74], and that of doxorubicin from pH-sensitive lipid cubic phase matrices [75], were described using the Higuchi law.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, hydrophilic drugs with different molecular weights, such as fluorescein, could be loaded into a liquid crystalline aqueous compartment and provided a cumulative drug release through the surfactant membrane, by a linear relationship between drugs and the square root of time, which has been also considered to be the Higuchi diffusion-controlled release kinetic [9]. Previous data demonstrated that the release of diclofenac salts from lyotropic liquid crystalline nanocarriers [73], as well as the release of charged molecules from lipid cubic phases, in a quasi-equilibrium process [74], and that of doxorubicin from pH-sensitive lipid cubic phase matrices [75], were described using the Higuchi law.…”
Section: Resultsmentioning
confidence: 99%
“…Cytotoxicity, apoptosis and pharmacokinetic experiments showed that the bioavailability of BF after encapsulation was significantly improved. The study exploited the structural features of the in situ phase transition from a microemulsion to a lyotropic liquid crystal toward the aim of controlled release of BF-loaded carriers [ 140 ].…”
Section: Strategies To Improve Solubility and Bioavailabilitymentioning
confidence: 99%
“…Consequently, the cubic or hexagonal phase can be dispersed in aqueous solutions forming cubic ("cubosomes") or hexagonal nanoparticles ("hexosomes") with an intact inner liquid crystalline structure and larger surface area but a lower viscosity [139]. An alternative strategy to improve their injectability is based on the use of a lower amount of viscous precursor (with a low amount of water): body fluids are taken up in vivo upon injection, resulting in the formation of a viscous depot system in situ [118,123,125]. A comprehensive overview about the detailed inner structure, preparation methods, and applications has been given in two recent reviews [140,141].…”
Section: Semi-solid Preparations and In Situ Forming Systemsmentioning
confidence: 99%
“…Narrow-sized water channels in the liquid crystal structure cause the sustained release behavior of low-molecular-weight drugs but might inhibit the release of molecules with higher molecular weight and therefore demand the addition of hydration-modulating agents [ 142 ]. The in vitro duration of action of the depot effect ranges from several days for bufalin [ 125 ], to 10 days for minocycline [ 126 ], or up to one month for leuprolide acetate [ 98 ], and can be easily tuned by adjusting the ratios of the used compounds [ 121 ]. A novel non-viral gene delivery system was designed by Borgheti-Cardoso et al, combining liquid crystals with polyethylenimine (PEI) to complex siRNA (small interfering RNA) [ 129 ].…”
Section: Semi-solid Preparations and In Situ Forming Systemsmentioning
confidence: 99%